2018
DOI: 10.3390/su10072512
|View full text |Cite
|
Sign up to set email alerts
|

A Conglomerate’s Effort for Co-Prospering with Its Subcontractors and Firm Value: Evidence from Korea

Abstract: Shared growth effort, which is also known as mutual growth, has emerged as one of the most important keywords in Korean economy. This study examines whether a conglomerate’s shared growth effort evaluated by the Shared Growth Commission is valued by market investors. Using our full sample, we find that firms participating in shared growth evaluation have a higher firm value. The results from the full sample show that firm’s effort on shared growth is rewarded in the Korean capital market. However, after matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…CSV has proved to be related to company value (Choi, Ko, & Jung, 2018). Specifically, in the tourism industry, several authors have linked specific hotel practices to CSV.…”
Section: Review Of the Literature And Research Hypothesesmentioning
confidence: 99%
“…CSV has proved to be related to company value (Choi, Ko, & Jung, 2018). Specifically, in the tourism industry, several authors have linked specific hotel practices to CSV.…”
Section: Review Of the Literature And Research Hypothesesmentioning
confidence: 99%
“…[35] have proved that a CSV strategy helps improving business competitiveness, underlining the importance of stakeholders' satisfaction in relation with this improvement. CSV also has a significant effect on the customer's behavioral intention [36] and finds benefit in the capital market [37]. From the point of view of sustainability at regional level, it has been demonstrated that the introduction of CSV strategies, resulted in the economic development of rural areas in the northeast of India and triggered the growth of women's crafting potential in the area [15].…”
Section: Advantages Of Csvmentioning
confidence: 99%
“…, 2016; Patatoukas, 2012) on the impact of buyer dominance over suppliers. When a buyer negotiates based on his/her strong market power, the supplier is forced to give up its incentive and accept lower payments for parts and materials (Choi et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Irvine et al, 2016;Patatoukas, 2012) on the impact of buyer dominance over suppliers. When a buyer negotiates based on his/her strong market power, the supplier is forced to give up its incentive and accept lower payments for parts and materials (Choi et al, 2018). Hence, risk-sharing benefits are less available for suppliers if there is a significant imbalance between buyers and suppliers (Hingley, 2005;Rokkan and Haugland, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation